4.1 Hyperalimentation and blood glucose control in very preterm infants: a randomised controlled parenteral nutrition study. (9th June 2014) - Morgan, C; Burgess, L; Grosdenier, M; Green, J; McGowan, P; Turner, MA
Abstract : Background: The Standardised, Concentrated with Added Macronutrients Parenteral (SCAMP) nutrition regimen is a method of hyperalimentation shown to improve early head growth in very preterm infants. 1 Early hyperalimentation is associated with marked hyperglycaemia. 2 Increasing early protein intake reduces the risk of insulin-treated hyperglycaemia. 3 We hypothesised that increasing both carbohydrate and protein intake simultaneously using the SCAMP regimen would not result in more insulin-treated hyperglycaemia. Methods: Control parenteral nutrition (PN) was started within 6 h birth and infants (<1200 g; <29 weeks) were randomised to either start SCAMP or remain on the control regimen. Actual nutritional intake, mean blood glucose (MBG) and insulin use data were collected for each day, d1–28. Results: Infants were randomised (d2–5) to SCAMP (n = 74) and control (n = 76) groups. SCAMP achieved higher mean actual protein/carbohydrate intakes from day 3–4. This was not associated with a difference in MBG or insulin use (Table 1 ). Conclusion: The SCAMP regimen did not result in the major disturbances in blood glucose control previously described with hyperalimentation. We propose this is partly explained by differences in early protein intake. References: Morgan C, McGowan P, Herwitker S, et al . Pediatrics 2014;133:e620–8 Tan M, Cooke RWI. Arch Dis Child Fetal Neonatal Ed 2008;93:F337–41 Mahaveer A, Grime C, Morgan C. Nutr Clin Pract 2012;27:399–405